2001
DOI: 10.1001/jama.286.18.2270
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Pharmacogenomics in Reducing Adverse Drug Reactions

Abstract: Our results suggest that drug therapy based on individuals' genetic makeups may result in a clinically important reduction in adverse outcomes. Our findings serve as a foundation for further research on how pharmacogenomics can reduce the incidence of adverse reactions and on the resulting clinical, societal, and economic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
289
1
20

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 637 publications
(313 citation statements)
references
References 64 publications
3
289
1
20
Order By: Relevance
“…Unfortunately, up to now, many liability genes explain less than 10% of the total variance, in the case of mood disorders as in many other fields of medicine, both for efficacy 2,51-55 and for side effect prediction. 56 Should we stop all our pharmacogenetic research then? Of course not, but knowledge is not a dichotomous issue, and partial information could be available at the beginning of the trial.…”
Section: Ethics Of Pharmacogenetics Beneficencementioning
confidence: 99%
“…Unfortunately, up to now, many liability genes explain less than 10% of the total variance, in the case of mood disorders as in many other fields of medicine, both for efficacy 2,51-55 and for side effect prediction. 56 Should we stop all our pharmacogenetic research then? Of course not, but knowledge is not a dichotomous issue, and partial information could be available at the beginning of the trial.…”
Section: Ethics Of Pharmacogenetics Beneficencementioning
confidence: 99%
“…Ferner spielen das Ausmaß der Affinität und eine eventuelle Inhibition eine Rolle (13). Vor allem für die polymorph exprimierten Enzyme CYP 2C9, CYP 2C19 und CYP 2D6 liegen Untersuchungen zur klinischen Relevanz vor (3,15,20) Ex-vivo lässt sich beispielsweise die Aktivität der ThiopurinMethyltransferase, bei der eine Defizienz in der heterozygoten Form bei etwa 10% der Bevölkerung vorliegt, im Plasma oder die der Alkohol-Dehydrogenase bestimmen (10). Dieses Verfahren wird allerdings nur in wenigen Zentren in Deutschland durchgeführt.…”
Section: Das Cytochrom-p450-system Und Seine Bedeutung Bei Arzneimittunclassified
“…When the parent drug is pharmacologically active, impaired enzyme function may increase the risk of developing adverse drug reactions (ADRs). For example, Phillips et al found that 59 % of drugs cited in ADR studies are, at least partially, metabolized by enzymes with reduced function [5]. Likewise, when metabolization results in inactivation of a parent drug, higher than normal enzyme activity may cause standard drug therapy to fail.…”
Section: Introductionmentioning
confidence: 99%